Association between depressive symptoms and sexual dysfunction in men with traumatic spinal cord injury - Ferro, Josepha Karinne de Oliveira; Silva, Caroline Palácio da; Oliveira, Daniella Araújo de (ABCS Health Sciences, 2019)
Introduction: Spinal cord injury results in loss of functional independence, autonomy and social status. This enormous change contributes to the appearance of depressive symptoms in this population. Objective: To evaluate depressive symptoms and sexual dysfunction in men with traumatic spinal cord injury, and to analyze their association. Methods: Observational study was performed with 44 men with traumatic spinal cord injury, age between 18 and 60 years, injury time over 1 year and active sexual life. The degree of neurological impairment was assessed through the revised 2011 ASIA Impairment Scale, depressive symptoms through the Beck Depression Inventory, and sexual function through the International Erectile Function Index. Descriptive statistics techniques and bivariate analysis were applied to verify association, using a level of significance of 0.05. Results: The volunteers had a mean age of 34.1 years, and an average injury time of 7.7 years. All individuals in the sample had lesion level above the medullary segment L2, with incomplete injury being the most frequent (68.2%). The mean time of the last sexual intercourse was 56.5 days and the weekly frequency of intercourse was the most reported (65.9%). Only 17.6% of the sample presented depressive symptoms, ranging from dysphoria (6.8%) to mild to moderate symptoms (6.8%). No association was found between depressive symptoms and sexual dysfunction, except for the domain of general satisfaction dysfunction (p=0.02). Conclusion: There is no association between depressive symptoms and sexual dysfunction in men with chronic spinal cord injury.